PSYCHOPATHIC BEHAVIOUR OF THE MAIN CHARACTERS IN TED TALLY’S MOVIE “THE SILENCE OF THE LAMBS” - Syam, Adeliah Nurmuthmainnah; Nur, Sahril; Iskandar, Iskandar (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
In this study, researcher analyzed the symptoms that arise from psychopathic disorder. The researcher analyzed 2 problems, they are: (1) What are the symptoms of the main characters potrayed in the movie